Astroglia in the Vulnerability to and Maintenance of Stress-Mediated Neuropathology and Depression - Miguel-Hidalgo, José Javier (Frontiers in Cellular Neuroscience, 2022)
Significant stress exposure responses and psychiatric depression are associated with morphological, biochemical, and physiological disturbances of astrocytes in specific brain regions relevant to the pathophysiology of those disorders, suggesting that astrocytes are involved in the mechanisms underlying the vulnerability to or maintenance of stress-related neuropathology and depression. To understand those mechanisms a variety of studies have probed the effect of various modalities of stress exposure on the metabolism, gene expression and plasticity of astrocytes. These studies have uncovered the participation of various cellular pathways, such as those for intracellular calcium regulation, neuroimmune responses, extracellular ionic regulation, gap junctions-based cellular communication, and regulation of neurotransmitter and gliotransmitter release and uptake. More recently epigenetic modifications resulting from exposure to chronic forms of stress or to early life adversity have been suggested to affect not only neuronal mechanisms but also gene expression and physiology of astrocytes and other glial cells. However, much remains to be learned to understand the specific role of those and other modifications in the astroglial contribution to the vulnerability to and maintenance of stress-related disorders and depression, and for leveraging that knowledge to achieve more effective psychiatric therapies.